Training Characteristics During Pregnancy and Postpartum in the World’s Most Successful Cross Country Skier - Solli, Guro S.; Sandbakk, Øyvind (Frontiers in Physiology, 2018)
This case-study investigated the training characteristics, physiological capacity and body composition of the world’s most successful cross country skier during the 40-week pregnancy, and the 61-week postpartum. Training data was systemized by training form (endurance, strength, and speed), intensity (low- (LIT), moderate- (MIT), and high-intensity training (HIT)), and mode (running, cycling and skiing/roller skiing). The training volume (mean±standard deviation(median)) during pregnancy was 12.9±7.3(10.0) h/wk in the first- (wk 1-12), 18.3±2.9(18.0) h/wk in the second- (wk 13-28) and 8.8±4.4(9.6) h/wk in the third trimester (wk 29-40). Endurance training time was distributed into 10.9±6.2(9.9), 15.2±2.3(15.6) and 7.6±3.8(7.9) LIT and 0.4±0.5(0.0), 1.3±0.4(1.4) and 0.7±0.6(0.8) h/wk MIT during the three trimesters. Only 2.2 h of HIT was performed during the entire pregnancy. During the first two trimesters, the distribution of exercise modes were approximately the same as pre-pregnancy, but the amount of running was reduced during the third trimester. Training volume during the postpartum periods 1-4 was 6.6±3.8(7.1) (PP1;wk 1-6), 14.1±3.4(14.3) (PP2;wk 7-12), 10.6±3.8(10.4) (PP3;wk 13-18) and 13.6±4.1(14.5) h/wk (PP4;wk 19-24), respectively. Training during PP3 and PP4 was interfered with two fractions in the sacrum, leading to decreased amount of running and MIT/HIT, compensated by increased amounts of cycling. Thereafter, training volume progressively approached the pre-pregnancy values, being 18.0±3.9(18.7) h/wk during the general preparation- (wk 25-44), 17.6±4.4(17.3) h/wk during the specific preparation- (wk 45-53) and 16.9±3.5(17.2) h/wk during the competition period (CP;wk 54-61) leading up to the subsequent world championship. The oxygen uptake at the estimated lactate threshold decreased to 90% of pre-pregnancy values in the second trimester, but remained to 100% in PP3. Body weight and fat-% was higher, while lean body mass and bone mineral density was lower after delivery compared to pre-pregnancy. These measurements gradually changed and were back to ∿pre-pregnancy values during CP. This study indicates that high-level cross country skiers can tolerate high training loads during pregnancy. Although the participant had some postpartum setbacks in her training due to fractures in the sacrum, reduced overall training load, followed by a slower progression and utilization of alternative exercise modes, led to a successful return to competitions.